Effect of pulsed electromagnetic field treatment on seed quality enhancement and storage in soybean - BHARAMARAJ BADIGER; RAVI HUNJE; N.K. BIRADAR PATIL; D.P. BIRADAR; VILAS A. TΟΝΑΡΓ (Seed Research, 2026)
An experiment was conducted to study the effects of pulsed electromagnetic field treatment on seed quality of fresh and revalidated seeds of soybean cv. JS9305 at Seed Quality Testing and Research Laboratory, National Seed Project (NSP), University of Agricultural Sciences, Dharwad. Seedswere exposed in four pulsed electromagnetic field treatment frequencies viz., control(untreated), 1Hz, 10Hz, 50Hz and 100Hz. The seed quality parameters were influenced by the pulsed electro-magnetic field treatment in both fresh and revalidated seed. Among the seed lot the effect of pulsed electromagnetic field treatments was more pronounced by recording higher seed quality parameter as compared to revalidated seed lot during the storage period. Irrespective of pulsed electromagnetic field treatments, significantly higher germination (61.87%), seedling dry weight (0.80g), vigour index (62), protein content(35.39%) and oil content (16.13%) of seeds recorded from the fresh seed lot (L₁) compared to revalidated seed lot (L₂) during the storage period. Among pulsed electromagnetic field treatments the 50Hz (F₁) recorded enhanced seed quality parameters by registering higher seed germination (62.67%), seedling dryweight(0.77g), vigour index (63), seed protein content (35.20%) and seed oil content (15.79%) compared to untreated seeds at the end of ten months of storage period.